Severe Hemolytic Jaundice in a Neonate with a Novel COL4A1 Mutation - Seiichi Tomotaki; Hiroshi Mizumoto; Takayuki Hamabata; Akira Kumakura; Mitsutaka Shiota; Hiroshi Arai; Kazuhiro Haginoya; Daisuke Hata (Pediatrics and Neonatology)
We report our experience with a preterm infant with severe hemolytic jaundice who required exchange transfusion just after birth. The patient was negative for alloimmune hemolysis as a result of maternal–fetal blood type incompatibility, and tests for inherited defects in erythrocyte metabolism, membrane function, and hemoglobin synthesis were normal. We also performed a bone marrow examination, but could not identify the cause of hemolysis. The patient had several other complications, including porencephaly, epilepsy, elevated serum levels of creatine kinase, and persistent microscopic hematuria. Later, we detected a genetic mutation in COL4A1, which was recently found to be associated with hemolytic anemia. We therefore believe that all of the patient's clinical features, including hemolytic anemia, were due to the mutation in COL4A1. Genetic testing for COL4A1 mutations is recommended in neonates who exhibit hemolytic disease of unknown etiology, especially when other complications compatible with COL4A1-related disorders are present.